The potential of Lumbricus rubellus as a bioaccumulator of excess Pb and Cd in organic media - M Arifin; Y Nuraini; W H Utomo; T Wardiyati (Brawijaya University, 2015)
Lead (Pb) and cadmium (Cd) are sources of serious problems in the environment due to their reactivity and toxicity. Lumbricus rubellus is an earthworm reared by people is expected to reduce Pb and Cd concentrations in the environments. The aim of this study was to explore the ability of Lumbricus rubellus in reducing excess of Pb and Cd in organic media generated from urban waste. Sixteen treatments (four levels of Pb concentration and four levels of Cd concentration) were arranged in a completely randomized design with three replications. Each treatment was placed in a wooden pot of 20 cm x 20 cm x 25 cm, and supplied with 40 Lumbricus rubellus for 30 days. Results of this study showed that 20 and 40% of the earthworm could survive until day 30 in organic media contaminated with Pb and Cd, respectively. Pb accumulated in the earthworm bodies ranged from 0.03 to 211.42 mg/kg, while the Cd accumulated in the earthworm body ranged from 0.57 to 22.11 mg/kg. The bioaccumulation factor for Pb was 46.98%, while that of Cd was 53.83%t. The content of Pb in vermicompost ranged from 0.04 to 19.41 mg/kg, while that of Cd ranged from 0.01 to 1.58 mg/kg.